Gastro-cutaneous fistula following anterior gastropexy. Issue 632 (June 1978) - Mackie, D. B.; Whitaker, M. J.; Gent, A. E.
Abstract : Two patients are described who developed a gastric fistula to the anterior abdominal wall following anterior gastropexy. Both fistulae closed spontaneously without any specific treatment. It is suggested that the fixation of the stomach to the anterior abdominal wall allows the fistula to discharge externally thus preventing peritoneal contamination with its serious consequences.